The Effects of Ubiquinol Intake and Sociophysical Training on the Activation of Psychological and Infrared Camera-Measured Body Temperature Physiology and Blood Molecular Markers: A Pilot Study among Healthy Female Older Adults - Makoto Ota; Masanori Hariyama; Ricki Colman; Mamiko Koshiba (Applied Sciences, 2024)
A combination of existing treatments with sensing technology may be the most appropriate approach for incurable neuropsychiatric disorders. Dietary antioxidant supplementation, exercise, and cognitive training are individually well-established treatments for neurodegeneration, Alzheimer’s disease, and other dementias. Therefore, in a double-blind randomized controlled trial, we evaluated the response of normal healthy older female subjects to coenzyme Q10 supplementation and simultaneous sociophysical training that was undertaken in a non-contact environment using infrared cameras. The current pilot study reports the results from a multivariate analysis of blood biomarkers, body surface temperature measured with infrared thermal cameras, and psychological questionnaire scores from this trial, in which 100 mg/day of supplemental ubiquinol (the reduced form of coenzyme Q10) was administered daily for one month. We found a significant positive correlation between ubiquinol supplementation and positive mood scores in the State–Trait Anxiety Inventory test (STAI-positive) and a weak inverse correlation between ubiquinol supplementation and serum interleukin 4 (IL-4), a systemic inflammatory marker. We also found a significant positive correlation between the standard deviation of body surface temperatures, detected with non-contact infrared image sensors, and both STAI-positive and serum antidiuretic hormone (ADH). The results from this small pilot study indicate the potential synergistic effects of oral ubiquinol intake and sociophysical training on neuropsychiatric health in healthy female older adults.